THE CIRCLE SYMBOL IN MUSIC EDUCATION - Ágnes GYOVAI; Tímea Mária HEVESI (Studia Universitatis Babeş-Bolyai. Musica, 2015)
In this paper, we examine whether the use of the circle symbol can enhance achieving this flow state, thus achieving deeper knowledge, and also, how the circle can be present in musical education. Through content analysis, we examine how the theory is put into practice, looking for the presentation of the circle symbol in dances, songs and other musical pieces. We reveal how and in what form, context and association the circle symbol appears in musical education. Our aim is to draw attention to the secrets of our surrounding world, the secrecy of the circle symbol in music. The circle, as a design in space, has a distinctive role in acoustic communication, which opens up the infinity of the musical cosmos through its individual and community building force. The ancient circle walks and dances are joint experiences of wholeness. The relevance of the research is the better understanding of the musical projection of the circle symbol, which can broaden perspective in school education.